L1-TV based image inpainting with denoising using interior point method - Concepcion, Rachel Anne G.; Neri, Marrick C. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2016)
Image restoration is an image processing method that attempts to bring back a damaged or degraded image into its original form. Two of the techniques which may be used to restor an image are inpainting and denoising. Image inpainting deals with restoring damaged portions on an image or covering unwanted regions present in it. This is done by using the information outside the area to be inpainted and extending it to the area to be inpainted. On the other hand, image denoising intends to come up with a clean version of a noise-corrupted image. In some cases, images which need to be inpainted are noisy.Thus, here is a need for the combinatio of the two processes. Solving the constructed lP using both feasibl and infeasible primal-dual interior point methods show that these methods are efficient for simultaneous inpaniting and denoising of images with impulse noise.
Thesis (M.S.-Applied Mathematics) --University of the Philippines Diliman
Keywords: Image stabilization; Inpainting